2013
DOI: 10.1111/1744-9987.12113
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte and Monocyte Adsorption Apheresis for Refractory Skin Diseases due to Activated Neutrophils, Psoriasis, and Associated Arthropathy

Abstract: Granulocyte and monocyte adsorption apheresis (GMA), an extracorporeal apheresis instrument whose column contains cellulose acetate (CA) beads, is designed to remove activated granulocytes and monocytes. We previously demonstrated that GMA was useful for treating neutrophilic dermatoses and associated arthropathy as it adsorbs Mac-1 (CD11b/CD18)-expressing neutrophils to the CA beads by the binding of complement component (iC3b) and CD11b expressed on activated neutrophils. The objective of this study is to fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 22 publications
0
37
1
Order By: Relevance
“…The efficacy of a twice-weekly regimen has not been confirmed for skin diseases, including PG (17), although the efficacy of the standard GMA regimen has been established in patients with corticosteroidand immunosuppressant-resistant PG (11,18). For the present case, we applied an intensive GMA regimen with corticosteroids in the expectation of a rapid improvement of severe skin and colonic mucosal lesions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The efficacy of a twice-weekly regimen has not been confirmed for skin diseases, including PG (17), although the efficacy of the standard GMA regimen has been established in patients with corticosteroidand immunosuppressant-resistant PG (11,18). For the present case, we applied an intensive GMA regimen with corticosteroids in the expectation of a rapid improvement of severe skin and colonic mucosal lesions.…”
Section: Discussionmentioning
confidence: 94%
“…Granulocyte and monocyte adsorption apheresis (GMA) was initially introduced for the treatment of UC (8)(9)(10), and its efficacy has also been confirmed for inflammatory disorders of the skin (11). Here, we report a case of PG associated with UC that showed dramatic response to the combination of GMA and corticosteroids.…”
Section: Introductionmentioning
confidence: 94%
“…Whether neutrophils have a causative role in the development of psoriasis lesions remains unclear, but their appearance in lesions precedes that of T-cells [49], and regions near neutrophil microabscesses show heightened mitosis and epidermal growth [24,50]. Prior studies have also demonstrated a correlation between lesion development and abundance of neutrophils in circulation [51,52], and reduction of peripheral neutrophils using adsorption apheresis was reported to improve psoriasis lesions in 39 of 44 patients [53]. Neutrophils also represent a source of cytokines demonstrated to drive lesion development, such as IL-17A, and indeed one study indicated that IL-17A(+) neutrophils are more abundant in lesions than IL-17A(+) T-cells [54].…”
Section: Discussionmentioning
confidence: 99%
“…GMA therapy has shown efficacy in several autoinflammatory and neutrophilic diseases such as PASH syndrome [17], DITRA (pustular psoriasis) [18], palmoplantar pustulosis [19], and Behçet's disease [20]. Although the efficacy of GMA therapy in Sweet's syndrome has been reported in 1 patient [14], it has not been fully described. In the present case, GMA therapy resulted in a rapid and significant response with reduced clinical symptoms and restoration of abnormal laboratory findings, similar to that reported in patients with the above diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, these agents sometimes cause adverse effects including serious infections, interstitial pneumonitis, and liver dysfunction. Although granulocyte and monocyte adsorption apheresis (GMA) therapy has significant efficacy with no safety concerns in pustular psoriasis [10, 11], ulcerative colitis [12], and pyoderma gangrenosum [13], its efficacy in Sweet's syndrome has only been reported in 1 case [14]. GMA is an extracorporeal apheresis that removes activated granulocytes and monocytes using a column packed with cellulose acetate beads (Adacolumn; JIMRO, Takasaki, Japan) [12].…”
Section: Introductionmentioning
confidence: 99%